Pengembangan Media Komik Audio Digital Untuk Meningkatkan Keterampilan Membaca Pemahaman Pada Mata Pelajaran Bahasa Indonesia Kelas V SDN Larangan 1 Utara - Salsabil, Zahra; Ritonga, Rudi (Academy of Education Journal, 2025)
This research aims to develop a digital audio comic as a learning media for the topic of facts and opinions in Indonesian language subject for fifth-grade students at SDN Larangan 1 Utara. The method used is Research and Development (R&D) with the ADDIE development model, consisting of five stages: Analyze, Design, Develop, Implement, and Evaluate. The media integrates visual elements in the form of digital comics and audio narration to enhance students' engagement and reading comprehension. Validation results from media experts, material experts, and language experts indicate that the developed media is appropriate for use. Small and large-scale trials show improvements in students' learning outcomes, proven by the comparison of pretest and posttest scores. Additionally, students responded positively to the media, stating it was interesting, easy to understand, and helpful in distinguishing between facts and opinions. Based on these findings, it can be concluded that the digital audio comic media is effective in improving elementary students’ reading comprehension skills.